What can machine learning do for information security?. Issue 4 (April 2019) - Mathews, Alex
Abstract : Machine learning is one of the most used and abused terms in information technology today. But what does it actually mean for the security community? When applied correctly, machine learning can significantly improve the effectiveness of security controls, but it is no cure-all. This is especially true while creating or refining a piece of software or an application: developers should first define the problem they want to solve and then select the most appropriate technology, instead of the other way around.